Short-Term Outcomes of Lower Trapezius Tendon Transfer With Achilles Allograft for Irreparable Posterosuperior Rotator Cuff Tears - Michael A. Stone, M.D; Liam T. Kane, B.S; Jason C. Ho, M.D; Surena Namdari, M.D (Elsevier, 2021)
Purpose: To evaluate functional outcomes, return to work, and reoperations associated with lower trapezius tendon transfer (LTT) for irreparable rotator cuff tears. Methods: This is a retrospective study performed by a single surgeon with minimum 1-year follow-up. LTT was performed using an open (n = 9; 60%) or arthroscopically assisted (n = 6, 40%) technique. Outcomes included failure rate, range of motion, satisfaction, return to work, and pre- and postoperative functional scores, as well as American Shoulder and Elbow Surgeons score, Single Assessment Numeric Evaluation, and the Simple Shoulder Test. Results: Fifteen patients were included. LTT was performed using an open or arthroscopically assisted technique. Mean age was 52 (range 31-62 years), 13 (92.9%) were manual laborers, and 9 (60%) had a worker's compensation claim. Three patients (20%) underwent conversion to reverse shoulder arthroplasty. Of the remaining 12 patients, there were significant improvements in American Shoulder and Elbow Surgeons, Single Assessment Numeric Evaluation, and Simple Shoulder Test at 24.1 ± 9.6 (range 12-38.5) months. Active forward elevation, abduction, and external rotation were all significantly improved. Postoperative satisfaction ratings indicated 67% of the revision-free cohort was "very satisfied" and 33% was "somewhat satisfied" with their outcome. Seven (50%) returned to full duty, 4 (28.6%) returned to modified duty, and 3 (21.4%) were unable to return to work. Two patients (open techniques) underwent a superficial wound debridement for seroma and wound breakdown. Conclusions: LTT results in successful clinical outcomes with a high rate of return to work in a challenging patient population. However, only 67% of patients rated themselves as "very satisfied," and 20% of patients were revised to reverse shoulder arthroplasty before 1 year. Limited preoperative active forward elevation (<90°) appears to predict poor functional results and risk for reoperation. Level of Evidence: Level IV, therapeutic case series.